Faktor-Faktor yang Mempengaruhi Penyaluran Kredit pada Bank Umum Periode 2008-2012 - Hasyim, Diana (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2014)
This research purposes to understand the direct and indirect impact of âThird Party Fundsâ, âNon Performance Loanâ, âReturn On Assetsâ and âCapital Adequacy Ratioâ to Banking Lending. Population of the research is âgo publicâ commercial bank in Indonesia in which 23 of them taken as sampel of research which were selected purposively based on the assumption that they became âgo publicâ in the period of 2008-2012. Whereas, the data analyzed by path analysis technique, while both ât-testâ and âcorrelation testâ were used in testing of hypothesis. Then, the finding shows that both variable of âthird party fundsâ and âreturn on assetsâ impact significantly to âCapital Adequacy Ratioâ. Furthermore, the âThird Party Fundsâ and âreturn on assetsâ impact positively to the Banking Lending, while Non-Performance Loan and Capital Adequacy Ratio impact significant negatively to Banking Lending